Sports injuries in German top level youth ice-hockey - epidemiology and prevention - Gramstat, B.; Henke, T.; Platen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Ice-hockey differs in dynamic, allowed body contact and equipment from other team sports. That`s why players are exposed to a high risk of injury and particularly young players should be protected against avoidable injuries. Aim of the study was to analyse the epidemiology of injuries in German top level youth ice-hockey and to provide information about typical injuries, injury risk and the cause of injuries. Methods: All teams (298 players and 10 coaches) of the german ice-hockey junior league (DNL) take part in the study during season 2013/2014. The survey was carried out by means of questionnaires, which were filled in in presence oft he interviewer. The questions covered - training and competiton exposition (hours), - age, height, weight, playing position and - most recent injuries of the last 18 months (diagnosis, treatment and time-loss, injury situation, protective equipment, position on the field at the time of injury). Results: 173 players (age: 16.92±1.0 years; height: 180.8±5.9 cm; body mass 77.34±7.6 kg) announced 141 injuries in the queried period (18 months) which were suffered to 64% in the competition and to 36% in the training. The most frequent injuries were concussions (13.5%), injuries of the acromioclavicular joint (11.3%) or the adductors (9.2%). Injuries of the shoulder had to be treated often inpatient (mean 2.8 days). In five of 31 cases it was necessary to operate. In the first half of the season 2013/2014 (3 months) the incidence for injuries in competition amounts to 0.38 injuries per game or 31,8 injuries per 1000 player-game hours. In the same period 15 players injured themselves in the training, it turns out an injury risk of 10.6 per 1000 training hours. Injuries of the adductors occurred to 75% in training sessions, mainly with the beginning of motion and/or while skating forward. According to the players 67% of the competition injuries were connected to irregular conduct of the opponent, though 73% of the breach of the rules wasn`t penalized by the referees. Discussion: On the basis of the findings, prevention measures should be age-related and addicted to the proficiency level of the player. 65% of the competition injuries were provoked by body contact, in literature values are between 45 -84 %. Irregular conduct must be penalized by the referees more strictly, referee`s performance should be standardised in youth ice-hockey. Injuries of the adductors can be reduced by specific prevention measures. Fairness and the respect for the opponent should be accepted and considered by all players equally, players should be sensitised for it already in their early stage of ice-hockey education. Besides education campaigns can cause a change in thinking.